Dietary supplementation with Moringa oleifera and mulberry leaf affects pork quality from finishing pigs. Issue 1 (5th October 2020) - Chen, Zujing; Xie, Yueqin; Luo, Junyi; Chen, Ting; Xi, Qianyun; Zhang, Yongliang; Sun, Jiajie
Abstract: Moringa oleifera and Morus alba leaves are nutritious non‐traditional feed ingredients containing bioactive substances. This study was to evaluate the potential application of dietary Moringa and Morus leaf powder on the growth traits, carcass characteristics and meat quality of finishing pigs. Moringa did not alter growth performance or carcass characteristics, but it decreased meat b* value, increased MyHCIIa and decreased MyHCIIx mRNA levels, and increased CP and concentrations of Ala, Thr, Ile, Lys and Pro in longissimus thoracis. Morus increased final BW, ADFI and ADG, decreased F/G ratio, improved slaughter weight, carcass weight, carcass yield and meat a* value, and decreased shear force, drip loss, MyHCIIx and MyHCIIb mRNA levels, and increased MyHCI and MyHCIIa mRNA levels. Morus also increased CP, Glu, Gly, Ala, Arg, Ile, Phe, Pro, Ser, Tyr and Asp, and C16:1, C18:1n9c, C20:4n6, C18:3n3, C20:3n3, C22:1n9 and n‐3 PUFA, but decreased C12:0 and C16:0. In summary, Morus improved the parameters and held great potential as an unconventional feed crop.